A cis-Divacant Octahedral and Mononuclear Iron(IV) Imide - Searles, Keith; Fortier, Skye; Khusniyarov, Marat; Carroll, Patrick J.; Sutter, Jörg; Meyer, Karsten; Mindiola, Daniel J.; Caulton, Kenneth G. (Angewandte Chemie International Edition, 2014)
A rare, low-spin Fe-IV imide complex [(pyrr(2)py)-Fe=NAd] (pyrr(2)py(2-) = bis(pyrrolyl)pyridine; Ad = 1-adamantyl) confined to a cis-divacant octahedral geometry, was prepared by reduction of N(3)Ad by the FeII precursor [(pyrr(2)py)Fe(OEt2)]. The imide complex is low-spin with temperature-independent paramagnetism. In comparison to an authentic Fe-III complex, such as [(pyrr(2)py)FeCl], the pyrr(2)py(2-) ligand is virtually redox innocent.
Keywords: density functional calculations; iron; magnetic properties; Mossbauer spectroscopy; N ligands